1998
DOI: 10.2190/p1hw-09jw-47pn-pnvd
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Attempt to Change Death Attitudes: Negative Findings and Associated Relationships

Abstract: Indirect treatment (concentrated relaxation and stress management) of student nurses did not produce a significant change in death anxiety or death depression or ability to communicate with the dying. Change in state anxiety and trait anxiety and general depression correlated with each other. Change in the three death attitude measures, however, neither correlated with each other nor with changes in the general anxiety and general depression measures. A viscosity model in which death anxiety and death depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Therefore, organizations can consider incorporating mindfulness training into their death‐related education and training programs. Finally, as Sliter, Sinclair, et al () note, because attitudes toward death may be difficult to change in a shorter time span (Rasmussen, Templer, Kenkel, & Cannon, ), death educational programs should be long‐term, intensive, and participative in order to be effective (Mooney, ).…”
Section: Implications For Practicementioning
confidence: 99%
“…Therefore, organizations can consider incorporating mindfulness training into their death‐related education and training programs. Finally, as Sliter, Sinclair, et al () note, because attitudes toward death may be difficult to change in a shorter time span (Rasmussen, Templer, Kenkel, & Cannon, ), death educational programs should be long‐term, intensive, and participative in order to be effective (Mooney, ).…”
Section: Implications For Practicementioning
confidence: 99%
“…In a more recent attempt to change death attitudes indirectly, Rasmussen, Templer, Kenkel, & Cannon (1998) used concentrated relaxation and stress management as a tool to try to reduce death anxiety in nursing students. They found no difference in death anxiety levels of their treatment group than the two control groups.…”
Section: Death Educationmentioning
confidence: 99%
“…Despite such a potentially debilitating condition, there are currently no effective ways to reduce death anxiety. Experimental studies are lacking, and the few studies that have been done found little support for behavioral approaches (e.g., systematic desensitization and relaxation; Rasmussen et al 1998;Testa 1981;White et al 1983White et al -1984 or life review therapy (Vaughan and Kinnier 1996). Other approaches, such as regret therapy (Tomer and Eliason 1996) or spiritual counseling (Eliason 2000), have not been subject to experimental investigation.…”
Section: Introductionmentioning
confidence: 99%